Expression of Recombinant Fusion Protein from Local Isolate of Newcastle Disease Virus and Antibody Response to Recombinant Fusion Protein in Broiler Chickens Post-Vaccination - Astuti, R.W.; Wijayanti, N.; Haryanto, A. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
This research aimed to express and purify the recombinant Fusion (F) protein of Newcastle Disease Virus (NDV) from a local isolate in Galur, Kulon Progo, Indonesia (0663/04/2013) from recombinant vector plasmid pBT7-N-His F, and to study the antibody response in the broiler sera which were injected with pure recombinant F protein compared with treated broilers that were vaccinated with commercial inactive NDV vaccines and control broilers without vaccination. The results showed that the recombinant F protein of NDV was successfully expressed, purified and visualized by SDS-PAGE with Coomassie Brilliant Blue staining and Westernblotting methods as a specific recombinant F protein with a molecular weight of 28 kDa. The pure recombinant F protein then was injected into broilers to determine the antibody response in broiler serum. Indirect ELISA showed that the production of antibodies was high in F protein vaccinated groups in comparison with other treated and control groups. The recombinant F protein has potential to be developed as a recombinant vaccine candidate after truncating the 6x His-tag part to obtain higher antibody respond if compared with antibody production in broiler serum post vaccinated with some commercially available broiler vaccines.